2010
DOI: 10.4103/0019-5545.74313
|View full text |Cite
|
Sign up to set email alerts
|

Children of men with alcohol dependence: Psychopathology, neurodevelopment and family environment

Abstract: Background:Children of people with alcohol dependence (COAs) are at high risk for behavioral and cognitive problems.Aim:Aim of this study was to compare the nature and extent of these problems in children of men with and without alcohol dependence.Materials and Methods:32 children (17 in study group and 15 controls) were evaluated for psychopathology, neurodevelopment, cognitive functioning and family environment. Tools used were: Socio-demographic data sheet, Malin’s Intelligence Scale for Indian Children (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Fathers or male figures in the household with alcohol-related problems or dependence was a negative predictor in two cohorts (EOI n = 1; IP n = 1). A father diagnosed with alcohol dependence was associated with lower cognitive scores in school children from India (B = -9.0, P uandj <0.05) [ 166 ]. A U.S. study found that in addition to the negative effects associated with prenatal marijuana exposure, children living with a male with alcohol-related problems scored 3.2 points lower than those without this exposure (P<0 .…”
Section: Resultsmentioning
confidence: 99%
“…Fathers or male figures in the household with alcohol-related problems or dependence was a negative predictor in two cohorts (EOI n = 1; IP n = 1). A father diagnosed with alcohol dependence was associated with lower cognitive scores in school children from India (B = -9.0, P uandj <0.05) [ 166 ]. A U.S. study found that in addition to the negative effects associated with prenatal marijuana exposure, children living with a male with alcohol-related problems scored 3.2 points lower than those without this exposure (P<0 .…”
Section: Resultsmentioning
confidence: 99%
“…[20] Thus, the mean IQ in our diabetic subjects is possibly lower than the normal population average. Findings from studies from the West have variably suggested that children with early diabetes onset (Ferguson et al ., 2005, Hannonen et al ., 2010, Naguib et al ., 2009)[212223], poor glycemic control (Ohmann et al ., 2010, Hannonen et al ., 2010, Naguib et al ., 2009),[182223] and episodes of severe hypoglycemia (Hannonen et al ., 2010)[22] may be at greater risk for lower neurocognitive performance.…”
Section: Discussionmentioning
confidence: 97%
“…Jogdand et al (2014) in India showed a clear association between alcoholism in the parent and overall higher odds of behavioural problems (Odds Ratio (OR) 1.56 (CI 1.12-2.17) p < 0.05) [47]. In another Indian study, Raman et al (2010) showed higher scores in externalisation behaviour (p < 0.01), but no significant difference in internalising behaviour [56]. In South Africa, Rochat et al (2019), children of mothers with hazardous drinking had higher mean scores for psychological problems (mean 45.0 if no hazardous drinking, 48.9 for hazardous drinking, p = 0.029) [60].…”
Section: Child Behavioural Problem or Disordermentioning
confidence: 95%
“…Similarly in Brazil, authors found children of alcoholics had a overall score in an academic performance test (which included reading and arithmetic), compared to children of non-alcoholic fathers [52]. Raman et al (2010) found, using Malin's Intelligence Scale for Indian children, mean score (93.28) for the verbal section in children of alcohol-dependent fathers was significantly lower than children of non-dependent fathers (107.1, p < 0.001) [56]. Similar results are found in performance (Mean score 95.7 vs 108.2 respectively, p < 0.01) and full-scale IQ test (Mean score 96.14 vs 105.1 respectively, p < 0.05).…”
Section: Child Cognitive Delay or Disordermentioning
confidence: 98%
See 1 more Smart Citation